Implementation of prophylactic and systematic tranexamic acid administration in the surgical safety checklist for adult patients: a protocol proposal - Pereira, Rita Q.; Leão, Diana C.; Mota, Teresa; Fernandes, Susana N.; Vargas, Susana; Abelha, Fernando; Almeida, Jorge; Paiva, José A.; Dias, José; Trindade, Eunice; Pimenta, Tiago; Azevedo, Ana; et al. (International Surgery Journal, 2025)
Background: The administration of tranexamic acid (TXA) in the surgical context has proven to be effective in reducing perioperative bleeding, both in cardiac and noncardiac surgery. Its low price and ease of use make it particularly advantageous. Despite existing evidence and international recommendations supporting its use in surgery, TXA remains underutilized and inconsistently used in surgery. Methods: Furthermore, integrating this recommendation into the 'safe surgery' approach by establishing a consistent process may enhance its beneficial effect on patient clinical outcomes. Therefore, to increase and standardize the use of tranexamic acid in surgery, we considered including prophylactic administration of TXA in the 'surgical safety checklist' (SSC) at our hospital and implemented a protocol for its systematic prophylactic administration in adult surgical patients at risk of moderate to high blood loss. Conclusions: A protocol based on current evidence, an innovative initiative implemented in a pioneering manner was presented at Unidade Local de Saúde São João.